2005
DOI: 10.1038/sj.npp.1300838
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol Reverses MK-801-Induced Disruption of Prepulse Inhibition in Mice

Abstract: Cannabidiol, a nonpsychoactive constituent of the Cannabis sativa plant, has been reported to act as an agonist of the vanilloid 1 channel in the transient receptor potential family (TRPV1) and also to inhibit the hydrolysis and cellular uptake of the endogenous cannabinoid anandamide. Cannabidiol has also been reported to have potential as an antipsychotic. We investigated the effect of cannabidiol on sensorimotor gating deficits in mice induced by the noncompetitive NMDA receptor antagonist, MK-801. Sensorim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
1
19

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(130 citation statements)
references
References 57 publications
6
104
1
19
Order By: Relevance
“…Strengthening these results, CBD reversed the disruption of prepulse inhibition (PPI) of the startle response in mice caused by MK-801, a glutamate receptor antagonist, as did clozapine, further supporting the idea that this compound may act as an atypical antipsychotic drug. 62 Consistent with the behavioral data, both CBD and clozapine, but not haloperidol, induced Fos immunoreactivity (Fos) in the prefrontal cortex, while only haloperidol increased Fos in the dorsal striatum. 63,64 Even in human models of psychotic symptoms induced in healthy volunteers, the antipsychotic-like activity of CBD can be demonstrated.…”
Section: Antipsychotic Actionsupporting
confidence: 70%
“…Strengthening these results, CBD reversed the disruption of prepulse inhibition (PPI) of the startle response in mice caused by MK-801, a glutamate receptor antagonist, as did clozapine, further supporting the idea that this compound may act as an atypical antipsychotic drug. 62 Consistent with the behavioral data, both CBD and clozapine, but not haloperidol, induced Fos immunoreactivity (Fos) in the prefrontal cortex, while only haloperidol increased Fos in the dorsal striatum. 63,64 Even in human models of psychotic symptoms induced in healthy volunteers, the antipsychotic-like activity of CBD can be demonstrated.…”
Section: Antipsychotic Actionsupporting
confidence: 70%
“…That study found that neither haloperidol nor clozapine reversed the effects of MK-801 on PPI. However clozapine has been reported by others to attenuate the effects of MK-801 on PPI in mice (Lipina et al 2005;Long et al 2006) but those studies did not test effects of a typical antipsychotic.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear how this effect would relate to the antipsychotic properties of CBD because usual antipsychotic drugs act by antagonizing dopamine-2 receptors [123]. Moreover, studies with animal models that involve dopaminergic stimulation suggest that the antipsychotic-like doses of CBD (60-120 mg kg 21 ) are higher than those needed to induce anxiolytic-like effects [7,91,92] and reverse behavioural deficits induced by the NMDA receptor antagonist MK-801 [93,94,99]. These findings indicate that the mechanisms of CBD effects on glutamateor dopamine-based models could be at least partially distinct.…”
Section: Cannabidiol and Psychosismentioning
confidence: 99%
“…This mechanism, probably by facilitating the pre-synaptic release of glutamate [80], is involved in the ability of CBD to reverse the disruption of PPI induced by the NMDA receptor antagonist MK-801 [93].…”
Section: Cannabidiol and Psychosismentioning
confidence: 99%